Morphological and ultrastructure alteration of larva Culex pipiens exposed from cassava juice extract - MARIA NINDATU; HERY JOTLELY; YOFIAN ANAKTOTOTY; MILDA RIANTY LAKOAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nindatu M, Jotlely H, Anaktototy Y, Lakoan MR. 2025. Morphological and ultrastructure alteration of larva Culex pipiens exposed from cassava juice extract. Biodiversitas 26: 306-314. Culex pipiens Linnaeus, 1758 is a mosquito commonly often found in residential areas, particularly in puddles of water and storage tanks. This mosquito serves as a vector for lymphatic filariasis in humans, also known as elephantiasis. To eliminate the transmission of elephantiasis, control strategies one are implemented targeting the growth of C. pipiens larval population. Cassava tubers have the potential as a biolarvicide to control the population and growth of C. pipiens mosquito larvae. This research was aimed to determine the phytochemical content and biolarvicide effectiveness of juice extract cassava (Manihot esculenta Crantz), which may cause damage to the head capsule, thorax, and abdomen of C. pipiens larvae. Phytochemical test on the cassava tubers juice extract (M. esculenta) revealed relatively high levels of flavonoids, ranging from 3 to 3.5 mg. The results of identification using a keyence 3D microscope show the fourth instar larvae of C. pipiens in the control group. The body color is pale, and the head and tail are brownish. Squeezed biolarvicide cassava tubers (M. esculenta) doses of 0.5, 1.5, and 3.5% caused larval mortality above 90% at the 6th hour for 24 hours. Further characterization using Scanning Electron Microscopy (SEM) indicated that a dosage of 3.5% applied for 24 hours caused significant damage to the head capsule, with the exoskeleton connecting the head and thorax nearly detaching. Higher concentration of cassava juice extract resulted in increased body damage to C. pipiens larvae. It can be concluded that the flavonoid compounds in cassava juice extract in this study can effectively damage the bodies of fourth instar C. pipiens larvae, as evidenced by the SEM results.